Gamification on Netboard: The Students’ Perceptions of its Practice in ESP Classroom - Fauzul Etfita; Sri Wahyuni; Estika Satriani; Asnawi Asnawi; Fermita Yuliasma (AL-ISHLAH: Jurnal Pendidikan, 2023)
Gamification is a learning approach that uses element from games to motivate students in the learning process and enhance feelings of enjoyment and engagement with the learning process This research aimed to investigate the students’ perception toward gamification as applied in English Language Education. This research was conducted at a private university in Riau, and the sample was 47 students of the sixth semester. This research used descriptive-quantitative approach, and the instrument is questionnaire. The questionnaire consists of 35 questions, divided into 7 indicators. The results of this study were processed quantitatively using the Likert scale formula. The result of this research indicates that students were dominant agreed with the 35 statements of 7 indicators about gamification. The research found that the 1st indicator agreed with index 68.65%, the 2nd indicator agreed with index 71.47%, the 3rd indicator agreed with index 68.65%, the 4th indicator agreed with index 67.16%, the 5th indicator agreed with index 71.1%, the 6th indicator agreed with index 71.7%, and 7th indicator agreed with index 70.8%. Therefore, gamification is a platform that suitable for teachers and students in the learning process, especially in learning English for specific purposes.